Delamination behavior of UHMWPE soft layered composites. (1st August 2016) - Meshi, Ido; Amarilio, Iris; Benes, Dana; Haj-Ali, Rami
Abstract: Ultra-high-molecular-weight polyethylene (UHMWPE) fiber based soft polymeric composite laminates are widely used in ballistic applications due to their high tensile strength and low density. The delamination between the layers is an important energy dissipation mode for ballistic resistance. In this study, two experimental setups are proposed and examined for the delamination behavior of UHMWPE composites. The first mode-I setup consists of a modified double cantilever beam (DCB) test. The second is a new interlaminar shear (ILS) test proposed to characterize delamination failure in mode-II, which is known to be a major drawback of these composites due to poor matrix-fiber interphase bond. Digital Image Correlation (DIC) method is employed to extract the full field shear strain in mode-II and to examine its uniformity. Crack length in mode-I was also quantified using optical means. Crack surfaces are characterized using Scanning Electron Microscopy (SEM) to study the propagation mechanism. The mode-I test results of commercial Dyneema HB26 (DH) cross-ply multi-layered composite provide insights on the material and crack behavior. The proposed ILS tests provide a unique way to impose close to uniform and dominant interlaminar shear strain. The ILS strength of DH is found to be significantly lower than its tensile strength.